Evaluation of a Patient Decision Aid for Refractive Eye Surgery - Subbaraman, Bhavani; Ahmed, Kamran; Heller, Matthew; Essary, Alison C.; Patel, Vimla L.; Wang, Dongwen (Applied Clinical Informatics, 2024)
Background We developed a prototype patient decision aid, EyeChoose, to assist college-aged students in selecting a refractive surgery. EyeChoose can educate patients on refractive errors and surgeries, generate evidence-based recommendations based on a user's medical history and personal preferences, and refer patients to local refractive surgeons.Objectives We conducted an evaluative study on EyeChoose to assess the alignment of surgical modality recommendations with a user's medical history and personal preferences, and to examine the tool's usefulness and usability.Methods We designed a mixed methods study on EyeChoose through simulations of test cases to provide a quantitative measure of the customized recommendations, an online survey to evaluate the usefulness and usability, and a focus group interview to obtain an in-depth understanding of user experience and feedback.Results We used stratified random sampling to generate 245 test cases. Simulated execution indicated EyeChoose's recommendations aligned with the reference standard in 243 (99%). A survey of 55 participants with 16 questions on usefulness, usability, and general impression showed that 14 questions recorded more than 80% positive responses. A follow-up focus group with 10 participants confirmed EyeChoose's useful features of patient education, decision assistance, surgeon referral, as well as good usability with multimedia resources, visual comparison among the surgical modalities, and the overall aesthetically pleasing design. Potential areas for improvement included offering nuances in soliciting user preferences, providing additional details on pricing, effectiveness, and reversibility of surgeries, expanding the function of surgeon referral, and fixing specific usability issues.Conclusion The initial evaluation of EyeChoose suggests that it could provide effective patient education, generate appropriate recommendations, connect to local refractive surgeons, and demonstrate good system usability in a test environment. Future research is required to enhance the system functions, fully implement and evaluate the tool in naturalistic settings, and examine the findings' generalizability to other populations.
Keywords: refractive surgical procedures; computer-assisted decision-making; patient education as topic; benefits and impact assessments; application of evaluation methodology evaluation guidelines